Mental Health Conditions and Nonpersistence of Direct Oral Anticoagulant Use in Patients With Incident Atrial Fibrillation: A Nationwide Cohort Study - Teppo Konsta; Jaakkola Jussi; Airaksinen K. E. Jussi; Biancari Fausto; Halminen Olli; Putaala Jukka; Mustonen Pirjo; Haukka Jari; Hartikainen Juha; Luojus Alex; Niemi Mikko; Linna Miika; et al. (Wiley, 2022)
BACKGROUND: Mental health conditions (MHCs) are associated with poor outcomes in patients with atrial fibrillation. However, persistence of oral anticoagulation therapy in patients with atrial fibrillation and MHCs is unknown. We aimed to evaluate the effect of MHCs on the persistence of direct oral anticoagulant (DOAC) use in patients with atrial fibrillation based on a nationwide cohort.METHODS AND RESULTS: The nationwide registry-based FinACAF (Finnish Anticoagulation in Atrial Fibrillation) cohort included 67 503 patients with incident atrial fibrillation and indication for permanent oral anticoagulation (CHA(2)DS(2)-VASc score >1 in men and >2 in women) starting DOAC therapy between 2011 and 2018. MHCs of interest were depression, bipolar disorder, anxiety disorder, schizophrenia, and composite of any MHC. The main outcome was nonpersistence of DOAC use, defined as the first 120-day period without DOAC purchases after drug initiation. The mean age of the patients was 75.3 +/- 8.9 years, 53.6% were women, and the prevalence of any MHC was 17.8%. Persistence after 1 year from DOAC initiation was 79.3% in patients without MHCs and 77.2% in patients with any MHC, and after 2 years were 64.4% and 60.6%, respectively (P<0.001). Higher incidence of nonpersistence to DOACs was observed in all MHC categories: adjusted subdistribution hazard ratios, 1.16 (95% CI, 1.11-1.21) for any MHC, 1.32 (95% CI, 1.22-1.42) for depression, 1.44 (95% CI, 1.15-1.80) for bipolar disorder, 1.25 (95% CI, 1.11-1.41) for anxiety disorder, and 1.30 (95% CI, 1.02-1.64) for schizophrenia. However, patients with only anxiety disorder without other MHCs were not at higher risk of nonpersistence.CONCLUSIONS: MHCs are associated with nonpersistence of DOAC use.